A fibra de vidro em matrizes poliméricas e cimentícias e seu uso estrutural em construção civil : o estado-da-arte - Ortenzi Junior, Altibano (2007)
This dissertation deals with the use of fiberglass as a concrete addition, in order to improve its mechanical properties such as better crack distribution, or as polymer reinforcement, in order to form a composite to be externally or internally used as reinforcement to other material as concrete or masonry or to use itself as a structural member. The literature review presented is believed to achieve the current state-of-art of the fiberglass use in civil construction applications. Next, usual approaches to dimensioning structural members in GFRP are presented. Construction systems and processes using this material are assessed focused to civil construction. Themes as the technology spread up, Brazilian applications and eventual difficulties are focused. With this research one expects to approach the text to the state-of-art up today.